A dimeric α-helical cell penetrating peptide mounted with an HER2-selective affibody. (26th August 2021) - Chong, Seung-Eun; Lee, Donghyun; Oh, Jae Hoon; Kang, Sunyoung; Choi, Sejong; Nam, So Hee; Yu, Jaehoon; Koo, Heebeom; Lee, Yan
Abstract : With the combination of a powerful cell penetrating peptide (CPP: LK-2) and an HER2-selective affibody (ZHER2:342 ), LK-2-ZHER2:342 showed remarkable selectivity on HER2-overexpressed cancer cells at nanomolar concentrations. Abstract : We have developed a cell penetrating peptide (CPP) system with high selectivity and penetrability at nanomolar concentrations with a combination of an HER2-selective affibody, ZHER2:342 (ZHER2 ), and a dimeric α-helical leucine- and lysine-rich peptide, LK-2. ZHER2 and LK-2 are linearly fused together and expressed in a prokaryotic system to create the LK-2-ZHER2 protein, which can successfully distinguish and penetrate HER2-overexpressing cancer cells at nanomolar concentrations. LK-2-ZHER2 has the ability to intracellularly deliver doxorubicin as a conjugate form to enhance its anti-cancer effect on HER2-overexpressing breast cancer cells with a great selectivity. The selective penetrability was confirmed in vitro, in 3D spheroids, and in in vivo models. LK-2-ZHER2 has the capability to overcome the weak points of current CPPs, such as poor penetrability at low concentrations and a lack of selectivity, by combining powerful CPP and affibody sequences.